Peran Serta Masyarakat Desa Adat Pakuseba Dalam Pengelolaan Daya Tarik Wisata Bali Taro Adventure Tours - Saskariana, I Wayan; Ariwangsa, I Made Bayu (JURNAL DESTINASI PARIWISATA, 2018)
Tourist attraction located in the traditional village environment it is believed will provide many benefits for the community, both directly involved in the management or that are not directly involved. This study aims to determine the participation by local communities in the management and Taro Bali Adventure Tours to determine the extent of the role played by the public. Data collection techniques in research using the method of direct observation location, interviews with two informants directed that Operational Managers and Kelihan Adat, as well as the documentation by taking pictures. The data obtained were analyzed using qualitative data analysis techniques that work with the data, organize data, search and find patterns, to get interesting data and specify the data to be lifted The results showed that the lack of direct participation in the management because there is no activity that can involve the community. Community participation has been limited to maintaining the security of the area yaang use and management in Taro Bali Adventure Tours has been done because it has future plans, oversight by the board of commissioners as representatives of the public and accountability of managers every month. Advice to public benefit and be directly involved in the management of Taro Bali Adventure Tours.   Keywords : Community Participation, Tourism Management, Bali Taro Adventure Tours